Revolução científica e nascimento da ciência experimental em Alexandre Koyré - Barbosa, Mohana Ribeiro (2013)
This work aims to understand the definition given by Alexandre Koyré for the experimental science of the seventeenth century, exploring the importance of this concept within the historiography of science. Assuming that the opposition made by Koyré of Auguste Comte’s positivism, theoretical conception dominant in the history and philosophy of sciences in the first half of the twentieth century, engenders a new meaning for science and its course. In his work as a historian of science, developed primarily between 1930 and 1961, Koyré formulates precise concepts for various elements considered essential to the history and philosophy of sciences, such as: scientific revolution, experimentation, tools and instruments. I intend to demonstrate the intellectual trajectory and epistemological debates present in the formation of these concepts.